Caves and the ancient Greek mind descending underground in the search for ultimate truth - Ustinova, Yulia; Oxford eBooks (Oxford : Oxford University Press, 2009)
A study of the way in which poets, priests, and sages sought for wisdom in ancient Greece by descending into caves or underground chambers. Yulia Ustinova offers a novel approach by juxtaposing ancient testimonies with the results of modern neuropsychological research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Caves -- Greece; Philosophy, Ancient; Mysticism -- Greece; Psychology, Religious; Electronic books